Modelling infiltration processes in rain gardens: Influence of design parameters on hydrological efficiency - M. Kravchenko; T. Tkachenko; V. Mileikovskyi (Екологічна безпека та збалансоване ресурсокористування)
A rain garden is a stormwater management system designed for on-site water control. Suboptimal rain garden designs may compromise hydrological performance during operation, necessitating developing and validating a mathematical model for engineering calculations and design assessment. This study aimed to model infiltration processes in a rain garden using a mathematical framework that accounts for the height of the water column (HWC) on the surface and the filtration coefficient of soil materials, simulating system behaviour during an extreme rainfall event (36 mm/h). The developed model generated performance curves illustrating the rain garden’s efficiency as a function of design parameters: construction depth, catchment-to-garden area ratio, filtration coefficient, and water retention capacity (WRC). Key soil material parameters were determined experimentally under laboratory conditions. The infiltration performance of the system was evaluated by analysing the variation in infiltration time, saturation of all layers, and the water filling level of the rain garden resulting from adjustments to its parameters and changes in HWC on the surface. The modelling results indicated that the primary parameters influencing the predicted time for complete system saturation and HWC formation are the catchment-to-garden area ratio and the filtration coefficient. The WRC of soil materials and the depth of the system layers significantly impact the time required for full saturation and water filling but have minimal effect on the surface HWC. It was demonstrated that a rain garden with a depth of 1.2 m, a catchment-to-garden area ratio of 15, and a filtration coefficient of 100-200 cm/h functions effectively under critical rainfall intensities. The developed model and the resulting data, providing precise calculations and design recommendations, can be utilised by engineers and planners to optimise rain garden designs, thereby enhancing stormwater management efficiency